PENGARUH ONLINE CUSTOMER REVIEW DAN ONLINE CUSTOMER RATING TERHADAP KEPUTUSAN PEMBELIAN MELALUI MARKETPLACE SHOPEE - Hasanah, Nurul; Syahrudin, Husni; Kuswanti, Heni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The study aims to determine: how much influence do online customer reviews and online customer ratings have on purchasing decisions through the Shopee marketplace of Economics Education students at FKIP Universitas Tanjungpura. This study uses a quantitative approach to the type of correlational research. The population in this study were regular Economics Education students class of 2017, 2018, 2019, 2020, and 2021. The sample in this study amounted to 96 students using a proportional stratified random sampling technique. Data collection techniques in this study used questionnaires and documentation. The research results showed that: online customer reviews and online customer ratings have a significant simultaneous effect on purchasing decisions through the Shopee marketplace of Economics Education students at FKIP Universitas Tanjungpura by 53.7% and the remaining 46,3% was influenced by other variables not examined, and also proven by fcount (53.919) ftable (3.09) and a significance level of (0.00) (0.05). The conclusion is that there is an influence of online customer reviews and online customer ratings on purchasing decisions through the Shopee marketplace of Economics Education students at FKIP Universitas Tanjungpura.